1982
DOI: 10.1002/chin.198213193
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: REACTION OF STERICALLY HINDERED O‐BENZOQUINONES WITH DIAZOMETHANE

Abstract: Äquimolare Mengen Diazomethan in Ether und 3,6‐Di‐tert.‐butyl‐o‐benzochinon (I) bilden als einziges Reaktionsprodukt das Indazol (II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Surprisingly, with a large excess of diazomethane, an inexplicable formation of benzodioxolane 54 was observed (Scheme 14). 29 Our investigations in this area revealed the propensity of o-quinones to react as a hetero-dipolarophile leading to the formation of a variety of densely functionalised spiro-heterocyclic compounds. It was observed that, unlike diazomethane, nitrile oxides undergo 1,3-dipolar cycloaddition reactions with substituted 1,2-benzoquinones at the carbonyl group to afford spirodioxazole derivatives.…”
Section: Huisgen 13-dipolar Cycloaddition Reactionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Surprisingly, with a large excess of diazomethane, an inexplicable formation of benzodioxolane 54 was observed (Scheme 14). 29 Our investigations in this area revealed the propensity of o-quinones to react as a hetero-dipolarophile leading to the formation of a variety of densely functionalised spiro-heterocyclic compounds. It was observed that, unlike diazomethane, nitrile oxides undergo 1,3-dipolar cycloaddition reactions with substituted 1,2-benzoquinones at the carbonyl group to afford spirodioxazole derivatives.…”
Section: Huisgen 13-dipolar Cycloaddition Reactionsmentioning
confidence: 98%
“…Surprisingly, little was known about the dipolar cycloaddition reactions of o-quinones except for a few reports on reactions with mesionic compounds 28 and diazomethane. 29 One of the first known examples of a dipolar cycloaddition of o-quinones involves the reaction of 3,6-di-tert-butyl-1,2benzoquinone 51 with an equimolar amount of diazomethane to afford the corresponding indazole derivative 52. With additional quantity of diazomethane, a methylene transfer reaction to one of the carbonyl groups leading to the formation of a spirooxirane 53 was observed.…”
Section: Huisgen 13-dipolar Cycloaddition Reactionsmentioning
confidence: 99%